Biology of Oysters - Bayne, Brian Leicester (Saint Louis : Elsevier Science, 2017)
'Biology of Oysters' is a definitive and comprehensive resource that offers deep insight into the scientific structure of oysters. Written by an expert in the field of shellfish research, this book presents more than 50 years of empirical research literature to equip researchers and students for learning about the unique issues within this field.
Models, Estuaries, and AquacultureBibliography; Chapter 5: Feeding; 5.1. Introduction; 5.2. Particle Uptake; 5.2.1. Particle Transport and Sorting Within the Pallial Cavity; 5.2.2. Morphological Variability of the Pallial Organs; 5.2.3. Selection and Selection Efficiency; The Physicochemical Bases of Selection; Selection Efficiency; The Costs of Selection; 5.3. Ventilation, Particle Capture, and Clearance; 5.3.1. Particle Filtration and Ambient Water Flow; 5.3.2. Measuring Feeding Behavior in the Field; 5.3.3. Particle Capture and Clearance; Methods; Relationships to Body Size.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 2, 2017).
Clearance Rate, Seston Quantity, and Seston Quality.
Text in English.
Keywords: Oysters; SCIENCE -- Life Sciences -- Zoology -- General; Oysters; Electronic books